Carcass wrote:
\((\frac{1}{2})^{-3}(\frac{1}{4})^{-2}(\frac{1}{16})^{-1}=\)
(A) \((\frac{1}{2})^{(-48)}\)
(B) \((\frac{1}{2})^{(-11)}\)
(C) \((\frac{1}{2})^{(-6)}\)
(D) \((\frac{1}{8})^{(-11)}\)
(E) \((\frac{1}{8})^{(-6)}\)
Nice rule: \((\frac{a}{b})^{-n} = (\frac{b}{a})^{n}\)\((\frac{1}{2})^{-3}(\frac{1}{4})^{-2}(\frac{1}{16})^{-1} = (\frac{2}{1})^{3}(\frac{4}{1})^{2}(\frac{16}{1})^{1}\)
\(= (2^{3})(4^{2})(16^{1})\)
\(= (2^{3})(2^{4})(2^{4})\)
\(= 2^{11}\)
\(= (\frac{2}{1})^{11}\)
\(= (\frac{1}{2})^{-11}\)
Answer: B